Myeloproliferative Neoplasm Symptom Assessment Form - Total Symptom Score (MPN-SAF TSS) questionnaire: translation, cultural adaptation and validation to Brazilian Portuguese - Mariana Guaraná; Andréa Soares; Adelmo Daumas; Irene Biasoli; Cristiana Solza (Hematology, Transfusion and Cell Therapy, 2022)
Introduction: Constitutional symptoms and thrombohemorrhagic events are common in patients with myeloproliferative neoplasms (MPNs). Hence, the treatment’s primary goal is to control symptoms and improve the quality of life (QoL). In order to assess response to therapy, symptom burden, and QoL among patients with MPN, the “Myeloproliferative Neoplasm Symptom Assessment Form - Total Symptom Score (MPN-SAF TSS)” questionnaire was developed in the USA in 2012. Herein, we translated and validated the MPN-SAF TSS questionnaire to Brazilian Portuguese. Methods: The ten-item questionnaire was translated from the English language and its psychometric properties (reliability, convergent and construct validities) were evaluated in 101 MPN patients. Results: There were 41 patients with essential thrombocythemia, 39 with myelofibrosis and 21 with polycythemia vera. The median age of all patients at diagnosis was 68 years and 59% were female. The Cronbach's alpha coefficient for the overall questionnaire was 0.78, ranging from 0.73 to 0.79, if each item was deleted. Validity analyses showed that the strongest item-item correlation were between early satiety and abdominal discomfort. Strong correlations were also found between physician and patient perceptions of itching (r = 0.81) and fatigue (r = 0.70). The Pearson coefficient correlation between the MPN-SAF TSS global score and the EORTC QLQ-C30 functional scales ranged from 0.51 to 0.64. The exploratory factor analysis showed that seven of the ten symptoms loaded into one single factor. Conclusion: The Brazilian Portuguese version of the MPN-SAF-TSS showed good psychometric properties and can be an available tool to assess symptom burden in this group of patients.